On eight species of the spider genus Synagelides Strand, 1906 from China (Araneae: Salticidae) - Wang, Cheng; Mi, Xiao-Qi; Irfan, Muhammad; Peng, Xian-Jin (European Journal of Taxonomy, 2020)
Six new species of Synagelides Strand, 1906 are diagnosed and described: S. bohdanowiczi sp. nov. (♂♀), S. leigongensis sp. nov. (♂♀), S. logunovi sp. nov. (♂♀), S. subgambosus sp. nov. (♂♀), S. wuliangensis sp. nov. (♂♀) and S. xingdouensis sp. nov. (♂♀). The female of S. forkiforma Yang, Zhu & Song, 2007 and the male of S. longus Song & Chai, 1992 are described for the first time. Photos of the habitus and copulatory organs, as well as a distributional map, are provided.